Do caregiver profiles predict the use of dementia care services? Findings from the Actifcare study. (1st February 2020) - Kerpershoek, Liselot; Woods, Bob; Wolfs, Claire; Verhey, Frans; Jelley, Hannah; Bieber, Anja; Stephan, Astrid; Michelet, Mona; Selbaek, Geir; Handels, Ron; Wimo, Anders; Hopper, Louise; et al.
Abstract: Objectives: Previously developed dementia caregiver profiles defined by caregiver age and burden, have been associated with caregiver quality of life, depression and perseverance time. The current aim was to investigate whether these caregiver profiles could predict subsequent service use. In addition, non-personal (e.g. meals on wheels) and supportive services (e.g. Alzheimer café) in early dementia were investigated as predictors. Methods: A total of 451 dyads of people with dementia and their informal caregivers from eight European countries were followed for one year. People were included if they did not use formal (personal) care but were expected to do so within 1 year. Logistic regression analyses were used with four clusters of service use as dependent variables (home social care, home personal care, day care and admission). The independent variables were caregiver profiles, and non-personal and supportive services at baseline. Results: Caregiver profiles were significant predictors of service use; those experiencing high strain were more likely to use formal care. The use of low-intensity, less intrusive services at baseline significantly predicted the use of home personal care and admission at follow-up. The use of day care at follow-up was predicted by the baseline use of supportive services. Conclusion: Caregiver profiles are valuable predictors for service use: this knowledge can aid professionals in ensuring optimal access to services, which is important for maintaining independence at home. In addition, the use of supportive and less intrusive, non-personal services in the early stages of dementia is to be advised.